Effect of Hormones on Direct Shoot Regeneration in Hypocotyl Explants of Tomato - Rizwan RASHID; Sarbjit Singh BAL (Notulae Scientia Biologicae, 2010)
This study was conducted for developing a high frequency regeneration system in two genotypes of tomato (Lycopersicon esculentum Mill.), Punjab Upma and IPA-3 for direct shoot regeneration from hypocotyl explants. The explants were excised from in vitro tomato seedlings and cultured on MS medium supplemented with different concentrations and combinations of hormones. Direct regeneration was significantly influenced by the genotype hormones combination and concentrations. The MS medium supplemented with (Kinetin 0.5 mg/l) and (BAP 0.5 mg/l) was found optimum for inducing direct shoot regeneration and number of shoots per explant from hypocotyl explants on this medium. Shoot regeneration per cent in Punjab Upma and IPA-3 per cent was recorded to be highest i.e (86.02) and (82.57) respectively. Besides this, average number shoots per explant was also highest i.e (3.16) in case of Punjab Upma and (2.93) in case of IPA-3. A significant decline was observed in percent shoot regeneration and average number of shoots per explant with increase in the hormonal concentration. Shoots were obtained and transferred to the elongation medium (MS + BAP 0.3 mg/l). Hundred per cent rooting was induced in separated shoots upon culturing on MS and MS basal media. Hardening on moist cotton showed maximum plantlet survival rate in case of both genotypes. After hardening, plants were transferred to soil. Thus, a tissue culture base line was established in tomato for obtaining direct regeneration using hypocotyl as explants.